Analisis Desain Layout Instagram Web Menjembatani Pengalaman Pengguna Instagram Mobile - Eric; Tan, Shinta; Muliadi, Wisnu (Fakultas Komputer - Universitas Universal, 2021)
Instagram Web can be accessed using a browser from a computer or laptop. Its function is the same as the Instagram application which was previously available on Android or IOS. The striking difference is the shape of the screen that displays content from Instagram users. This journal will discuss how the design of the user interface and user experience balances the Instagram web and is not disconnected from the design of the Instagram application on Android. The result of the research is that Instagram Web Design creates a design that follows the initial purpose of the Instagram mobile application design which is related to the principles of value, desirability, adoptability, and usability. That way the Instagram Web user experience can be aligned with the Instagram mobile user experience.